Cost effectiveness of telephone follow up for paediatric patients with epilepsy in Hospital Universiti Sains Malaysia Kelantan - Girubaharan, Jovitra (2014)

(untitled)
Background Childhood epilepsy is a condition that has a wide possibility of causes. Most of the children with epilepsy also suffer from other complications either from the underlying condition or epilepsy itself. It is of utmost importance that these children are followed up to ensure that their illness is controlled and to help them achieve a good quality of life. However frequent clinic visits for follow up appointments have placed a high financial burden on most families and is also a cause of defaults for appointments. The high patient load in clinics from these frequent appointments have also placed a burden on the hospitals in terms of cost and labour force needed. The purpose of this study is to use the telephone as a tool for follow up of patient’s well-being and control of seizures at home. This does not require them to come to the hospital and would reduce the financial burden to both, the family of the child and the hospital. Method The study was a pilot study and was conducted in the Paediatric Neurology clinic of HUSM from June 2013 till February 2014. It involved a total of 68 children with epilepsy aged 2 years till 21years who fulfilled the study inclusion criteria. They were divided into two arms, one arm had a telephone follow up in the following three months and the other arm had a clinic appointment. Results The results showed significant reduction in cost in the telephone follow up group as compared to the conventional clinic follow up with no significant increase in morbidity or mortality. The average cost to Hospital USM for clinic follow up was RM 25.57 per patient whereas the cost for telephone follow up averaged RM 4.86 per patient. The cost to patients for clinic follow up averaged RM 44.85 and a consultation via telephone averaged RM 1.84, as the phone calls were made by the hospital. Conclusion The cost effectiveness analysis has quantitatively showed in this pilot study that it is more cost effective to the hospital if patients with chronic disease who needed regular follow up could be followed up with telephone consultation.